Implicit time-place conditioning alters Per2 mRNA expression selectively in striatum without shifting its circadian clocks. Issue 1 (December 2018) - Shrestha, Tenjin; Šuchmanová, Karolína; Houdek, Pavel; Sumová, Alena; Ralph, Martin
Abstract Animals create implicit memories of the time of day that significant events occur then anticipate the recurrence of those conditions at the same time on subsequent days. We tested the hypothesis that implicit time memory for daily encounters relies on the setting of the canonical circadian clockwork in brain areas involved in the formation or expression of context memories. We conditioned mice to avoid locations paired with a mild foot shock at one of twoZeitgeber times set 8 hours apart. Place avoidance was exhibited only when testing time matched the prior training time. The suprachiasmatic nucleus, dorsal striatum, nucleus accumbens, cingulate cortex, hippocampal complex, and amygdala were assessed for clock gene expression. Baseline phase dependent differences in clock gene expression were found in most tissues. Evidence for conditioned resetting of a molecular circadian oscillation was found only in the striatum (dorsal striatum and nucleus accumbens shell), and specifically forPer2 expression. There was no evidence of glucocorticoid stress response in any tissue. The results are consistent with a model where temporal conditioning promotes a selectivePer2 response in dopamine-targeted brain regions responsible for sensorimotor integration, without resetting the entire circadian clockwork.